The Analysis of Swear Words in Instagram Comments Column of @lilnasx Account - Nuriah Allailah, Sri; Febryanto, Mohammad; Hasti, Siti (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
This research focuses on the swear words on Instagram because so many swear words can be found on social media. The Instagram @lilnasx account is one of the examples gets swear words from social media users, especially since he is famous. This research used qualitative research method to analyze swear words in Instagram comments column of @lilnasx account taken from June to September 2022. This research showed that there are four types and five functions of swear words. The types of swear words found are one dysphemistic, 30 idiomatically, 31 abusively, and 38 emphatically from 100 comments. Meanwhile, the functions of swear words found are 23 abusive, 19 humoristic, 20 expletive, three euphemistic, and 35 habitual from 100 comments.